Epidemiological and demographic characteristics of dengue and chikungunya infections over five years from 2014-2018, in Tamil Nadu, India - Velusamy, Dhanalakshmi; Jayakumar, Suriakumar; Ramakrishnan, Varatharaj; Veeramanoharan, Rajamannar; Gupta, Bhavna; Paramasivan, Rajaiah; Ramasamy, Vasanthapriyan Moongilpatti (International Journal Of Community Medicine And Public Health, 2021)
Background: An epidemiological, demographic and seasonal trend analysis of dengue and chikungunya seroprevalence was performed in five districts of Tamil Nadu during 2014-2018. Methods: Serum samples from the suspected patients were screened using IgM antibody ELISA. Results: Dengue and chikungunya seropositivity ranged from 17.9-68.2% and 14.9-58.3%, respectively. Dengue cases were reported in all the years with a spike in 2017. Highest number of chikungunya cases was in 2018. Dengue cases peaked in the cooler months following monsoon while chikungunya data for seasonal trend analysis was not sufficient. Both viral infections were found common in the people >12 years, however, the difference of cases between males and females was not statistically significant. Conclusions: The findings of this study indicate that both chikungunya and dengue are actively circulating in the state and the state health department needs to direct their efforts not only to control the spread but also on the future preparedness to prevent outbreaks.